An-Na'im's Nasakh and the Flexibility of Islamic Law - Asman, Asman (Sharia and Law Faculty, 2023)
This study analyzes the thoughts of Abdullahi Ahmed an Na'im in the reform of Islamic law, Abdullahi Ahmed an-Na'im is one of Sudan's intellectual figures. The purpose of this study is to uncover conceptual textual thinking, an object of study that is placed as part of the study of Islamic law studies in reform. This critical study emphasizes the need for a review of the naskh principle, for an-Na'im, which lies in the necessity to treat the texts of Al-Quran in a relevant manner in order to realize an adequate reform of Islamic law in a modern context. By understanding the texts of the verses in the Al-Quran as a form of delaying their implementation until the right time, he uses the logic or reverse paradigm of the conventional textual principles, namely by re-effective the principles of Islamic teachings contained in the verses of the Mecca phase, which in conventional text theory is stated to have been by later Madaniyyah verses. For him, reversing the naskh process is an evolutionary principle of interpretation. The method used is descriptive, hermeneutic, and phenomenological methods. Practically speaking, his textual thought, which is aimed at making the interpretation of Islamic teachings relevant in the context of the modern world, can be useful in its application for the good and benefit of the ummah in the renewal of Islamic law in the reform of Islamic law. Kajian ini menelaah pemikiran dalam pembaharuan hukum Islam, Abdullahi Ahmed an-Na’im merupakan seorang tokoh intelektual dari Sudan. Arah tujuan dari kajian ini diarahkan untuk mengungkap pemikiran naskh secara konseptual, sebuah objek kajian yang diletakkan bagian dari kajian pembaharuan hukum Islam. Dalam pembahasan ini menjelaskan bahwa perlunya adanya kajian ulang terhadap prinsip-prinsip naskh an-Na'im, bagi yang harus segera diluruskan adalah harus memperlakukan teks-teks al-Quran secara relevan demi mewujudkan sebagai pembaruan hukum dalam Islam yang sesuia dengan perkembangan zama modern. Dengan menafsirkan teks-teks ayat-ayat Al-Qur'an sebagai bentuk penundaan eksekusi sampai waktu yang tepat, ia menggunakan logika atau pola terbalik dibandingkan dengan prinsip tekstual biasa, yaitu dengan menegaskan kembali prinsip-prinsip doktrin Islam yang ditemukan dalam ayat-ayat periode Mekah, yang menurut teori naskah umum dikatakan terkandung dalam ayat-ayat Madaniyyah yang kemudian beredar. Bagin Abdullahi Ahmed an-Na'im, membalikkan proses naskh adalah prinsip interpretasi evolusioner Metode yang digunakan metode deskriptif, hermeneutika, dan fenomenologi. Secara praktis, bahwa pemikiran naskhnya yang ditujukan untuk merelevansikan penafsiran ajaran Islam dalam konteks dunia modem, dapat berguna penerapannya bagi kebaikan dan kemaslahatan umat dalam pembaharuan hukum Islam dalam reformasi hukum Islam.